Bombus Latreille and Psithyrus Lepeletier of "Parco Naturale dell'Adamello" (Centrai Alps) (Hymenoptera Apidae Bombinae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The species of Bombus Latreille and Psithyrus Lepeletier collected in an interestingprotected area of Central Alps ("Parco Naturale dell'Adamello") are listed.They are 24 species (18 Bombus, 6 Psithyrus), besides two more Bombus capturedjust outside the border of Pàrco. This set of Bombinae can be considered completefor the investigated area and very important with regard to the preservation of theenvironment.
Keywords: Bombus; Psithyrus; distribution; Parco Adamello